(3QSGdI aj ChGFd cJH GdMOjKs - (3SfHd , eMeO SYjO Hf eMeO SfHd GdeLdGFj,J (B1175 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ Edi Gddg eMeO SYjO Hf eMeO SfHd WdH efi ef dg MSf Xf Hi Cf CSeYg TjFkG ef ChGFd cJH GdMOjK GdeTghQI aCLHJg dPGdc aCMHHJ Cf CdNU eeG PcQ ajg Chd MOjK ef cd JCdja s
(3BNQgG (B:s
(3aVd GdEjeGf Yf YHGOI Hi GdUGeJ QVi Gddg JYGdi Yfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3ef TgO Cf dG Edg EdG Gddg hMOg dGTQjc hGf eMeO YHOg hQShdg hCf YjSi YHO Gddg hQShdg hcdeg CdbGgG Edi eQje hQhM efg hGdLfI Mb hGdfGQ Mb CONdg Gddg JYGdi GdLs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B36s
(3eUOQ GbJfGA GdCUd (B:s
(3GdSYjOjI GdYGeI HJhfc (B((3CUhd MOjK (B39) s
Keywords: (3GdMOjK h GdeUWdMs